2021
DOI: 10.3389/fnut.2021.756193
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Ferroptosis Subtypes With Distinct Immune Infiltration and Gender Difference in Gastric Cancer

Abstract: Background: Iron is an essential nutrient involved in the redox cycle and the formation of free radicals. The reprogramming of iron metabolism is the main link to tumor cell survival. Ferroptosis is an iron-dependent form of regulated cell death associated with cancer; the characteristics of ferroptosis in cancers are still uncertain. This study aimed to explore the application value and gender difference of ferroptosis in prognosis and immune prediction to provide clues for targeted therapy of gastric cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
(54 reference statements)
1
6
0
Order By: Relevance
“…Therefore, these results detailed the conditions and ways in which FRGs regulate GC development, which may be conducive to further study of immune escape surveillance. In addition, ferroptosis-related reactive oxygen species and iron uptake could lead to somatic nonsynonymous mutations and microsatellite instability, resulting in increasing immunogenicity and immune infiltrates [47,48], which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, these results detailed the conditions and ways in which FRGs regulate GC development, which may be conducive to further study of immune escape surveillance. In addition, ferroptosis-related reactive oxygen species and iron uptake could lead to somatic nonsynonymous mutations and microsatellite instability, resulting in increasing immunogenicity and immune infiltrates [47,48], which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with non-malignant cells, the growth of cancer cells is strongly dependent on the micronutrient iron (ferrum in Latin), which is necessary for the ferroptosis process and can be inhibited by various iron-chelating agents. The excessive iron load may lead to ferroptosis in cancer patients [ 60 – 62 ], membrane transferrin receptor 1 (TFR1) can transport Fe 3+ ions into cells [ 63 ], was also recently identified as a biomarker for ferroptosis [ 63 ]. Under the action of DMT1, Fe 3+ is converted to Fe 2+ .…”
Section: Iron Metabolismmentioning
confidence: 99%
“…Studies have found that ferroptosis plays a critical role in the carcinogenesis and progression of GC ( Gomaa et al, 2019 ; Liu Y. et al, 2021 ). The levels of ferroptosis were related to a variety of prognosis and cancer immune characteristics, which might be conducive to the individualized treatment of GC ( Ma et al, 2021 ).…”
Section: Ferroptosis and Gastric Cancermentioning
confidence: 99%